RANCANGAN SISTEM HIDROLIK ALAT BANTU PENGANGKAT DAN PENURUN INTEGRATED DRIVE GENERATOR PADA PESAWAT AIRBUS 320 DI PT. GARUDA MAINTANANCE FACILITY AERO ASIA - Ade Alfiansyah. S; Ego Widoro; Djudjur Prasodjo (Langit Biru: Jurnal Ilmiah Aviasi, 2019)
When lowering and lifting the IDG with a weight of 56 kilograms in the IDG replacement process is done by positioning body that is not in a safe position. This is due to the unavailability of tools for IDG installation on Airbus 320 aircraft. Based on these problems, it is necessary to use IDG lifting and lowering devices with a hydraulic system. The first step to complete the design of the hydraulic system in this tool is to know the weight of the upper frame and the load from IDG so that the hydraulic system components needed such as actuators, hand pumps, flexible hoses, hydraulic fluids and fluid storage tanks can be calculated. The design of this tool uses an actuator with an inside diameter of 2.216 inch, an outside diameter of 2,294 inches and a length of 5 inches. Hydraulic hose with 0.223 inch inside diameter and outside diameter of 0.236 inch. Hand pump with a capacity of 1,376 inch3 and tank volume 19,811 inch3 . This tool can be used to assist the remove and installation of integrated drive generators on Airbus A320 aircraft at PT. Garuda Maintenance Facility after going through several test.